GAME ACTIVITY AS THE MAIN FORM OF WORK WHEN TEACHING STUDENTS FOREIGN LANGUAGES - Ishonkulov Sherzod Usmonovich (Modern American Journals, 2025)
This article explores the efficacy of game activity as a primary pedagogical strategy in foreign language (FL) education. While traditional methodologies often emphasize rote memorization and grammatical drills, modern communicative approaches increasingly recognize the need for engaging, low-stress environments that foster authentic language use. Game activity, including role-plays, simulations, and language-focused games, is examined for its capacity to significantly enhance student motivation, reduce affective filter, and provide meaningful context for language practice. The research synthesizes existing theoretical frameworks and empirical evidence to establish the game as a central, rather than supplementary, form of work for developing communicative competence across all language skills (listening, speaking, reading, and writing) and linguistic components (vocabulary and grammar).
Keywords: Foreign language teaching, game activity, communicative competence, student motivation, language acquisition, task-based learning, role-play, engagement.